Profile of elderly patients who suffered trauma im Londrina - Paraná - Biazin, Damares Tomasin; Rodrigues, Rosalina Aparecida Partezani (Revista da Escola de Enfermagem da USP, 2009)
The objective of this study is to characterize elderly victims of traumas admitted to three tertiary hospitals in Londrina, Paraná State. This quantitative-based research lasted six months and was carried out by means of an observational and cross-sectional study of 121 elderly people (60 to 74 years old) and their caregivers at the patients' homes, by the use of interviews. Results indicated that the majority of the elderly patients were males, with average age of 67.7 years. The suffered traumas were distributed as follows: 62.0% by falls; 25.6% by transport accidents; and 10.4% by other sources. As a consequence of the trauma, the elderly patient had from one to three injuries and 11 (9.1%) died. Falls were the major source of traumas. This event can be avoided by the observations of predisposing intrinsic and extrinsic factors, aiming at establishing prevention strategies to this type of trauma.